Sustainable Finished Product Optimization on Quality Response and Attitudinal Parameters - Nur Qurratul Ain, Adanan; Faiz, Mohd Turan; Kartina, Johan (Springer, 2021)
In this demanding polymer production industry such as injection molding process where the quality of the product is the most critical concerns, it is necessary to have a systematic production planning and routine analysis. But, contemporary production is no longer possible without an efficient and permanent search for better quality especially on sustainability optimization of the system. So, there is a need for consideration on sustainability capable improving the variables that can affect quality and are a result of the human factors’ action must be optimised within the plastic injection moulding (PIM) process. Consequently, this paper focused on the optimisation for quality response and attitudinal attributes that influenced sustainable PIM for both technical and management in order to meet optimum sustainable product quality.